Food mixing : principles and applications - Cullen, P. J. [ (Patrick J.)] (Wiley-Blackwell, 2009)
Presents information on the principles and applications of mixing within food processing. This work addresses the underlying principles of mixing, equipment design, novel monitoring techniques and the numerical techniques available to advance the scientific understanding of food mixing. It describes food mixing applications in detail.